2022
DOI: 10.2991/assehr.k.220204.058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Administrative Services Quality on the Public Satisfaction in the Land Certificate Program at the National Land Agency (BPN) of Tangerang City

Abstract: Many problems arise in the public services provided by the National Land Agency (BPN) of Tangerang City to administer public land certificates. The topic raised in this research is public service at the National Land Agency of Tangerang City. The essence of the vision of public service is the realization of excellent public services, which means realizing public satisfaction to get services from government agencies. A high level of public satisfaction is a sign that an organization is successfully performing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The community perceived all TERRA dimensions of service quality as good. The research of Sari et al (2022) also indicated the influence of five dimensions on the service quality.…”
Section: Community Perceptions On Land Service Quality Dimensionsmentioning
confidence: 90%
See 2 more Smart Citations
“…The community perceived all TERRA dimensions of service quality as good. The research of Sari et al (2022) also indicated the influence of five dimensions on the service quality.…”
Section: Community Perceptions On Land Service Quality Dimensionsmentioning
confidence: 90%
“…Saad & Alshehri (2021) indicated the reliability dimension that had positively affected the service quality. Sari et al (2022) also indicated the influence of reliability dimension on the service quality.…”
Section: Community Perceptions On Reliability Dimension Of Land Servi...mentioning
confidence: 95%
See 1 more Smart Citation